A Study and Availability Assessment of Freshwater Crabs in the Hill Streams of Bangladesh - Rajib Hasan; Harun Or Rashid (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2016)
A study of crabs was conducted at eight hill streams, located in three different districts of Bangladesh, during January to December, 2012 with a view to assess the availability and to studythe taxonomy of freshwater crabs. The study investigated species diversity which includes their taxonomic description, biometric data, habitat, ecological note, distribution, and ecological role. The specimens were collected in different times covering the major seasons rounded the year by using various fishing gears such as cast net, push net, dip net, seine net and trap. A total four species of freshwater crabs under two families (Potamidae and Grapsidae) were recorded. The identified four crabs were Sartoriana spinigera, Sartoriana trilobata, Labothelphusa wood-masoni and Pyxidognathus fluviatilis. Among these the first three were under the family Potamidae and the last one under the family Garapsidae. Sartoriana trilobata was the dominant species in the hill streams of Bangladesh.